Revue Faire 16 - 30. - Langdon, James; Bosshard, Ariane; Martin, Julie; Huz, Olivier; Dupeyrat, Jérôme; Lebrun, Olivier; Parcollet, Remi; Bruet, Manon; Guiral, Catherine; Hervy, Étienne (Paris : Empire Editions, 2019)
verzameling van 15 nummers van het tijdschrift Revue Faire : nº 16 — A reproduction: what El Lissitzkzy wants. Author: James Langdon nº 17 — An acronym: ACAB. Authors: Ariane Bosshard, Jérôme Dupeyrat, Olivier Huz and Julie Martin nº 18 — A studio visit: Ines Cox. Authors: Manon Bruet and Julia Andréone nº 19 — A history: graphic designer-publishers. Author: Thierry Chancogne nº 21 — An original: The Most Beautiful Swiss Books 2004–2006. Interview with Laurent Benner by James Langdon, photos: Andrian Samson nº 20 — A ski resort: Pierre Faucheux and Les Arcs. From the space to the sign. Author: Catherine Guiral nº 22 — • SPECIAL ISSUE • Artists Posters. Authors: Thierry Chancogne, Jérôme Dupeyrat, Mathias Augustyniak nº 23 — A portrait: The Master approving of his own work. Author: Ziga Testen nº 24 — A theater identity: The Schauspielhaus Zürich by Cornel Windlin. Authors: Étienne Hervy Chancogne nº 25 — Exhibition views? Jonathan Monk. Author: Remi Parcollet nº 26 — Production process: Print on Demand. Author: Manon Bruet nº 27 — Rhizomes of London: Archigram and mental images of the city. Sonia de Puineuf nº 28 — The conference: a format. Author: Manon Bruet nº 29 — Girls, the Troopers of Dance. Aesthetization of Politics and Manipulation of Entertainment. Author: Alexandra Midal nº 30 — Types of types: the typographic specimen by Lineto. Author: Olivier Lebrun
boek